Inter‐individual variability in atrasentan exposure partly explains variability in kidney protection and fluid retention responses: A post hoc analysis of the SONAR trial. Issue 2 (26th November 2020) - Koomen, Jeroen V.; Stevens, Jasper; Bakris, George; Correa‐Rotter, Ricardo; Hou, Fan Fan; Kitzman, Dalane W.; Kohan, Donald; Makino, Hirofumi; McMurray, John J. V.; Parving, Hans‐Henrik; Perkovic, Vlado; Tobe, Sheldon W.; et al.
Abstract: Aim: To evaluate whether atrasentan plasma exposure explains between‐patient variability in urinary albumin‐to‐creatinine ratio (UACR) response, a surrogate for kidney protection, and B‐type natriuretic peptide (BNP) response, a surrogate for fluid expansion. Methods: Type 2 diabetic patients with chronic kidney disease (n = 4775) received 0.75 mg atrasentan for 6 weeks in the active run‐in period. Individual area under the concentration‐time‐curve (AUC) was estimated using a population pharmacokinetic model. The association between atrasentan AUC, other clinical characteristics, and UACR and BNP response, was estimated using linear regression. Results: The median atrasentan AUC was 43.8 ng.h/mL with a large variation among patients (2.5th‐97.5th percentiles [P]: 12.6 to 197.5 ng.h/mL). Median UACR change at the end of enrichment was −36.0% and median BNP change was 8.7%, which also varied among patients (UACR, 2.5th‐97.5th P: −76.2% to 44.5%; BNP, 2.5th‐97.5th P: −71.5% to 300.0%). In the multivariable analysis, higher atrasentan AUC was associated with greater UACR reduction (4.88% per doubling in ng.h/mL [95% confidence interval CI: 6.21% to 3.52%], P < .01) and greater BNP increase (3.08% per doubling in ng.h/mL [95% CI: 1.12% to 4.11%], P < .01) independent of estimated glomerular filtration rate, haemoglobin or BNP. Caucasian patients compared with black patients had greater UACR reduction (7.06% [95% CI: 1.38% to 13.07%]) and also greater BNP increase (8.75% [95% CI: 1.65% to 15.35%]). UACR response was not associated with BNP response (r = 0.06). Conclusion: Atrasentan plasma exposure varied among individual patients and partially explained between‐patient variability in efficacy and safety response.